Seven-layer deep neural network based on sparse autoencoder for voxelwise detection of cerebral microbleed - Zhang, Yu-Dong; Zhang, Yin; Hou, Xiao-Xia; Chen, Hong; Wang, Shui-Hua (Multimedia tools and applications, 2018)
In order to detect the cerebral microbleed (CMB) voxels within brain, we used susceptibility weighted imaging to scan the subjects. Then, we used undersampling to solve the accuracy paradox caused from the imbalanced data between CMB voxels and non-CMB voxels. we developed a seven-layer deep neural network (DNN), which includes one input layer, four sparse autoencoder layers, one softmax layer, and one output layer. Our simulation showed this method achieved a sensitivity of 95.13%, a specificity of 93.33%, and an accuracy of 94.23%. The result is better than three state-of-the-art approaches.